Asistensi Penyusunan Naskah Proposal Penelitian Dan Pengabdian Masyarakat Dengan Metode Lgd (Leaderless Group Discussion) Di Universtias Kadiri - Prasetyawan, Fendy; Saristiana, Yuneka; Dhafin, Anis Akhwan; Mildawati, Ratna; Muslikh, Faisal Akhmal; Ariawan, Wahyu (Gotong Royong, 2024)
The assistance program for drafting research and community service proposals using the Leaderless Group Discussion (LGD) method at Universitas Kadiri aims to enhance the capacity of lecturers and students in producing high-quality and relevant proposals. The LGD method allows each participant to actively engage in discussions without a dominant leader, fostering involvement and constructive collaboration. The program includes preparation, workshop implementation, proposal evaluation, and follow-up stages. Results indicate significant improvements in problem formulation clarity, methodological accuracy, and proposal consistency. Additionally, active participant involvement and the development of collaborative skills were achieved, strengthening an inclusive discussion culture within the academic environment. Evaluations show that the LGD method effectively enhances academic and professional quality, despite challenges in ensuring deep understanding of topics and methodologies. With support from the Universitas Kadiri's Center for Educational Development and Quality Assurance (LP3M) team, this program successfully met its objectives and provides a strong foundation for similar future activities. The outcomes of this program are expected to contribute to improving the quality of innovative and impactful research and community service.